The Ancient Oriental Treaty and the Form of the Covenant in the Old Testament - McCarthy, Dennis J. (1962)
I. The Ancient Treaties: The Barliest Material – Hittite Treaties (Parity and Vassal Treaties) – Syria – Assyria – Conclusions. II. The Old Testament: Deuteronomy – I. II. Samuel – Joshua – Sinai – Conclusions; Dissertation.